Repositioning the State Administrative Court within the Electoral Justice System: Implications of Decision No. 82/G/2020/PTUN.JKT on the Finality of DKPP Decisions - Rino Irlandi; Nur Ali Rahman (Simbur Cahaya, 2026)
The normative final and binding nature of the Election Organisers Honour Council (DKPP) decisions creates a complex juridical dilemma when they are followed up as a State Administrative Decree (KTUN) by executive agencies. Following the issuance of the Jakarta State Administrative Court (PTUN) Decision No. 82/G/2020/PTUN-JKT, a widespread academic misconception emerged, mistakenly assuming it as an expansion of PTUN's authority into electoral disputes. In reality, the genuine legal gap lies in the blurred legal demarcation line between upstream ethical violations and downstream state administrative disputes. This doctrinal legal research aims to rectify the theoretical basis of such judicial competence and formulate the ideal repositioning of the PTUN within the electoral justice system. Using statutory, case (ratio decidendi), and conceptual approaches, the legal materials were qualitatively analysed through deductive reasoning. The results demonstrate that the PTUN operates strictly within the corridor of conventional administrative disputes, serving as a procedural guardian and a reviewer of the legality of administrative execution rather than an electoral judge. Under the doctrine of derivative invalidity, it is established that upstream formal procedural defects committed during DKPP hearings (violations of notification deadlines and the audi alteram partem principle) automatically infect and invalidate the downstream execution decree. Consequently, the absolute finality of DKPP decisions collapses into "quasi-finality," reinforcing the inherent relationship between public ethics and administrative law, while shifting the paradigm toward the supremacy of procedural justice. To resolve this, positive law reform is required by amending Article 458, paragraph (13) of the Election Law to explicitly limit PTUN's competence for judicial review to the authority and procedural aspects of execution, and by internalising due process of law standards within DKPP's procedural law.